The Use of Social Networking Sites in Mental Health Interventions for Young People: Systematic Review - Ridout, Brad; Campbell, Andrew (Journal of medical Internet research, 2018)
The onset of mental health problems peaks between adolescence and young adulthood; however, young people face barriers to treatment and are often reluctant to seek professional help. Many are instead seeking support and information regarding their mental health via the Web, especially via social networking sites (SNSs), and hence, there is a promising opportunity to use SNSs to deliver or integrate with youth-focused online mental health interventions. Previous reviews have evaluated the effectiveness of SNSs for specific disorders in young people; however, none of the reviews have covered the breadth of SNS-based youth mental health interventions available across all mental health issues. This review aimed to systematically identify available evidence regarding the use of SNS-based interventions to support the mental health of young people aged up to 25 years, to evaluate their effectiveness, suitability, and safety, and identify gaps and opportunities for future research. The PubMed and PsycINFO databases were searched using Medical Subject Headings terms and exploded keywords and phrases. Retrieved abstracts (n=974) were double screened, yielding 235 articles for screening at the full-text level. Of these, 9 articles met the review inclusion criteria. Given the small number of studies, and the variety of outcome measures used, a quantitative meta-analysis was not possible. The 9 articles (quantitative studies, qualitative studies, and descriptions of the iterative design process) covered 5 separate interventions. Of the 5 interventions, 2 interventions used purpose-built platforms based on the moderated online social therapy (MOST) model, 2 used Facebook, and 1 evaluated a purpose-built mobile app. The 2 MOST interventions targeted specific mental health issues (depression and psychosis), whereas the others focused on improving mental health literacy, social support, and general well-being. Only 3 quantitative studies were identified, and all used a pre-post design (without a control group) to establish proof of concept. Of the outcome variables assessed, there were significant improvements in mental health knowledge and number of depressive symptoms but no improvement in anxiety or psychosis symptoms. Acceptability of and engagement with the SNS platforms were generally high, as were perceptions of usefulness and safety. Moderation by clinical experts was identified as a key component of the more successful interventions. When offered a choice, users showed a preference for mobile apps over Web-based interfaces. The evidence reviewed suggests young people find SNS-based interventions highly usable, engaging, and supportive. However, future studies need to address the current lack of high-quality evidence for their efficacy in reducing mental health symptoms. Given young people are already turning to SNSs to engage in knowledge seeking and peer-to-peer support, SNS-based youth mental health interventions provide an opportunity to address some of the barriers young people face in accessing qualified mental health support and information.